Critical Perspectives on Human Security: Rethinking Emancipation and Power in International Relations - Chandler, David; Hynek, Niklas (PRIO New Security Studies, 2011)
This new book presents critical approaches towards Human Security, which has become one of the key areas for policy and academic debate within Security Studies and IR. The Human Security paradigm has had considerable significance for academics, policy-makers and practitioners. Under the rubric of Human Security, security policy practices seem to have transformed their goals and approaches, re-prioritising economic and social welfare issues　that were marginal to the state-based geo-political rivalries of the Cold War era. Human Security has reflected and reinforced the reconceptualisation of international security, both broadening and deepening it, and, in so doing, it has helped extend and shape the space within which security concerns inform international policy practices. However,　in its wider use, Human Security has become an amorphous and unclear political concept, seen by some　as progressive and radical and by others as　tainted by association with the imposition of neo-liberal practices and values on non-Western spaces　or as legitimizing attacks on Iraq and Afghanistan. This book is concerned with critical perspectives towards Human Security, highlighting some of the tensions which can emerge between critical perspectives which discursively radicalise Human Security within frameworks of emancipatory possibility and those which attempt to deconstruct Human Security within the framework of an externally imposed attempt to regulate and order the globe on behalf of hegemonic power. The chapters gathered in this edited collection represent a range of critical approaches which bring together alternative understandings of human security. This book will be of great interest to students of human security studies and critical security studies, war and conflict studies and international relations. David Chandler is Professor of International Relations at the University of Westminster. He is author of several books and edits the Journal of Statebuilding and Intervention . Nik Hynek is Research Fellow at the Institute of International Relations in Prague and Lecturer at Charles University and Metropolitan University. Previously, he conducted research at the Saltzman Institute of War and Peace Studies (SIWPS) at Columbia University and at the BIOS Institute of the LSE. He has widely published on international security and theories of IR. 1. Introduction: Emancipation and Power in Human Security Nik Hynek and David Chandler Part I 2. ‘We the Peoples’: Contending Discourses of Security in Human Rights Theory and Practice Tim Dunne and Nicholas J. Wheeler 3. Development of the Human Security Field: A Critical Examination David Bosold 4. Post-Colonial Hybridity and the Return of Human Security Oliver P. Richmond 5. Towards a Critical Security Paradigm? Reconceptualizing the ‘Vital Core’ of Human Security Giorgio Shani 6. Human Security, Biopoverty and the Possibility for Emancipation David Roberts 7. Institutionalised and Co-opted: Why Human Security Has Lost Its Way Mandy Turner, Neil Cooper and Michael Pugh Part II 8. The Limits to Emancipation in the Human Security Framework Tara McCormack 9. Rethinking Global Discourses of Security David Chandler 10. Human Security and the Securing of Human Life: Tracing Global Sovereign and Biopolitical Rule Marc G. Doucet and Miguel de Larrinaga 11. Problematising Life under Biopower: A Foucauldian versus an Agambenite Critique of Human Security Suvi Alt 12. Rethinking Human Security: Economy, Governmentality and Hybridization of Individuals Nik Hynek 13. Human Security: Sovereignty, Citizenship, Disorder Kyle Grayson 14. Inhuman Security Mark Neocleous